(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The work of the “indigenous atalayeros”, which is reported from the first years of the Colonial times in Yucatan, appears primarily with the characteristics of a personal service, although later it is hidden like a benefit to the king, and later on like a public load. However, at anyone of the denominations it hid in an open way the usufruct that was made of the work of the natives. This distribution service has not been considered up to now in the studies of the personal service in Mexico.